The Effect of Personal Hypertension Management Program (HMP) Education on Self-Efficacy in Hypertension Management in Outpatients at the Hospital 'Aisyiyah Pariaman Year 2024 - Alpices; Junios; Apriadi, Dwi (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
This study aims to determine the effect of personal hypertension management program education on self-efficacy in hypertension management. This research is a quasy experiment design with a non-equivalent control group design. The number of samples in this study was 30 respondents who were divided into two groups, namely 15 intervention group respondents and 15 control group respondents. Sample grouping in this study was carried out randomly for the experimental group and the control groupThe intervention group is respondents who are given personal hypertension management program education and the control group is respondents who are not given personal hypertension management program education. The data analysis used was the T-test (Independent Sample T-Test). Personal education was conducted for 3 weeks by providing hypertension management program personal education one session per week, for 15-20 minutes. The study found that most respondents (60%) had poor self-efficacy in the intervention group respondents before being given personal education based on a hypertension management program and most respondents (93.3%) had efficacy after being given personal education based on a hypertension management program. From the bivariate analysis results, there is a mean change in self-efficacy in intervention group respondents with the control group, where the mean difference value is 3.067. The T-test value is 2.579 with a p-value = 0.015 where the p-value ≤ 0.05, which means that there is an effect of personal education based on HMP on self-efficacy in respondents after being given personal education interventions based on a hypertension management program. The provision of personal education interventions based on a hypertension management program shows the results of the average change in the self-efficacy of respondents in the intervention group before and after being given personal education based on a hypertension management program and there is no average change in the self-efficacy of respondents in the control group who are not given personal education based on a hypertension management program